Open fetal surgeries in two dogs - Kalkan, C.; Aydin, M.; Saat, N.; Dogan, H.; Ocal, H.; Risvanli, A. (Wiley-Blackwell, 2014)
[Abstract Not Available]
18th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- SEP 11-13, 2014 -- Helsinki, FINLAND